Accuracy of the lamellar body count in amniotic fluid contaminated by meconium*. (January 2015) - Fields, Meredith; Towers, Craig V.; Howard, Bobby C.; Hennessy, Mark D.; Wolfe, Lynlee; Weitz, Beth; Porter, Stephanie
Abstract Objective: To determine whether meconium-contaminated amniotic fluid falsely elevates the lamellar body count in fetal lung maturity testing. Methods: Thirty mothers undergoing amniocentesis for fetal lung maturity testing were prospectively consented. A 2 mL portion of the patient's sample was mixed with a 10% meconium solution and the meconium-stained sample was then run in tandem with the patient's sample used in clinical management. Pure meconium samples without amniotic fluid were also run through the cell counter for analysis. Results: Following meconium contamination, the lamellar body count value increased in 67% of the cases, decreased in 23% and remained the same in 10%. There were 13 test results that had "immature" values in the uncontaminated patient management sample group and nine of these (69%) became elevated to a "mature" level (a false elevation) following the addition of meconium. All of the 10 pure liquid meconium samples devoid of amniotic fluid processed by the cell counter identified and quantified some particle the size of platelets. Conclusions: The lamellar body count test result is not reliable in meconium-stained amniotic fluid specimens. There is some unknown particle found in meconium that is the size of platelets/lamellar bodies that can falsely elevate the test result. Currently, the only reliable fetal lung maturity test in meconium-stained amniotic fluid is the presence of phosphatidylglycerol.